A preparation method and application of hard carbon negative electrode material for sodium ion battery
By using a circulation pump to perform efficient pickling in the preparation of hard carbon anode material of sodium ion batteries, the problems of long pickling time and low efficiency in the prior art are solved, and efficient preparation of hard carbon anode material and excellent electrical electricity are achieved Chemical properties.
Patent Information
- Application Number
- CN202310867267.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The existing pickling process of hard carbon anode materials of sodium ion batteries has problems such as long pickling time and low efficiency, which leads to prolonging production cycle, large equipment investment, high cost, and difficult to apply in large-scale production.
By mixing the carbon source precursor with the acid solution, and circulating the mixed liquid with a circulation pump, efficient pickling of the carbon source precursor is achieved, and then carbonization is carried out to improve the electrochemical performance of the hard carbon negative electrode material.
It significantly improves the pickling efficiency, reduces production time and cost, and is suitable for the preparation of large-scale hard carbon anode materials. The obtained hard carbon anode material has excellent impurity removal effect, sodium storage performance, charge and discharge capacity and Coulomb efficiency.
Smart Images

Figure CN116692829B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a preparation method and application of a hard carbon negative electrode material for a sodium ion battery. Background Art
[0002] Due to the sharp fluctuations in the price of lithium carbonate, the lithium-ion battery industry has been greatly impacted, and similar sodium-ion batteries have been able to develop rapidly. Sodium resources are widely distributed, low-cost, and non-strategic metals. Large-scale application has become imperative, and it has absolute application prospects as a supplement to lithium-ion batteries.
[0003] Commonly used negative electrode materials for sodium ion batteries include natural graphite, artificial graphite, and hard carbon materials. The acid washing and purification process of natural graphite is relatively mature, while the acid washing process of hard carbon materials and their precursors is still under exploration. Chinese patent CN110148734A discloses using rice husks, coconut shells, reed stalks, etc. as carbon sources, heat treating the carbon sources at 600-1100°C, crushing them, and then using ultrasonic acid washing to remove impurities in hard carbon materials to improve their electrochemical properties. Chinese patent CN108975304A uses pepper as a carbon source, and after pre-carbonization, high-temperature carbonization, and annealing, it uses acid / alkali solution washing for 1-10 hours to prepare hard carbon negative electrode materials.
[0004] However, the pickling processes disclosed in the above patents all have the disadvantages of long pickling time and low pickling efficiency. The inefficient pickling process will extend the production cycle of the hard carbon negative electrode material, or cause a large amount of equipment investment, which is not conducive to capacity planning and production costs; and the disclosed pickling processes are mostly based on laboratory gram-level tests with low solid content and the ultrasonic dispersion method used cannot be applied in large-scale production processes. Therefore, there is an urgent need for a preparation method for hard carbon negative electrode materials with high pickling efficiency. Summary of the invention
[0005] In order to solve the above problems, one object of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery, which improves the pickling efficiency of the carbon source precursor and has a better pickling effect.
[0006] The second object of the present invention is to provide an application of a hard carbon negative electrode material for a sodium ion battery.
[0007] To achieve the above-mentioned purpose of the invention, the technical solution of the method for preparing the hard carbon negative electrode material for sodium ion batteries of the present invention is:
[0008] A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: mixing a carbon source precursor and an acid solution to obtain a mixed solution, circulating the mixed solution under the action of a circulating pump, acid washing the carbon source precursor, filtering, washing and drying, and then carbonizing the carbon source precursor under an inert atmosphere.
[0009] The preparation method of the hard carbon negative electrode material for a sodium ion battery provided by the present invention allows the mixed liquid to circulate under the action of a circulating pump, so that the slurry circulates up and down, and the hydrophobic carbon source precursor and the acid solution are fully mixed, thereby improving the effective contact between the acid solution and the carbon source precursor, and significantly improving the pickling efficiency. The hard carbon negative electrode material after pickling has a low ash value and has excellent impurity removal and pickling effects. The obtained hard carbon negative electrode material has excellent sodium storage performance and has high charge and discharge capacity and coulomb efficiency.
[0010] The method for preparing a hard carbon negative electrode material for a sodium ion battery provided by the present invention is simple, does not require a large amount of equipment, can greatly reduce production time and cost, and is suitable for the preparation of large-scale hard carbon negative electrode materials.
[0011] In order to make the impurity removal more thorough and improve the pickling effect, preferably, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, acetic acid, and citric acid. More preferably, the acid solution is selected from one or more of hydrochloric acid, nitric acid, and hydrofluoric acid.
[0012] In order to improve the impurity removal effect, preferably, the mass fraction of the acid solution is 0.5-5wt%, and more preferably, the mass fraction of the acid solution is 0.5-4wt%.
[0013] In order to further improve the impurity removal effect, preferably, the acid solution contains at least hydrochloric acid and hydrofluoric acid, and the mass fraction ratio of the hydrochloric acid to the hydrofluoric acid is 2-3:0.5-1.
[0014] In order to improve the sodium storage performance of the hard carbon negative electrode material, preferably, the carbon source precursor is selected from one of coal and a carbonized material, the coal is selected from one or more of anthracite, bituminous coal, lignite, and lignite, the carbonized material includes one or more of fruit shell carbonized material, charcoal, bamboo charcoal, resin carbonized material, and polymer carbonized material, and the fruit shell in the fruit shell carbonized material is selected from one of coconut shell, walnut shell, peach shell, jujube shell, apricot shell, cherry shell, pistachio shell, and macadamia shell.
[0015] In order to further improve the pickling efficiency, preferably, the particle size of the carbon source precursor is less than 2 mm. The carbon source precursor is coarsely crushed to a particle size less than 2 mm, and the coarse crushing includes jaw crushing and roller crushing. More preferably, the carbon source precursor is air flow crushed after coarse crushing to a particle size D 50 More preferably, the particle size D 50 5~10μm.
[0016] In order to improve the effective contact between the carbon source precursor and the acid solution and improve the impurity removal effect, preferably, the solid content of the carbon source precursor in the acid solution is 5-30%, and the acid washing time is 10-50 minutes. More preferably, the solid content of the carbon source precursor in the acid solution is 15-25%.
[0017] In order to make the acid solution and the carbon source precursor more effectively contact and improve the impurity removal effect, preferably, the circulating pickling is to use a circulating pump during the pickling process, and the circulating pump is selected from one or more of a centrifugal pump, a screw pump, a shear pump, a smooth pump, an emulsification pump, a pneumatic diaphragm pump, and a high viscosity pump. More preferably, the circulating pump is one of an emulsification pump and a shear pump.
[0018] In order to achieve a better carbonization effect, preferably, the particle size D of the carbon source precursor for the carbonization treatment is 50 The carbonization temperature is 1000-1600°C and the treatment time is 1-10 hours. More preferably, the carbonization temperature is 1100-1400°C and the treatment time is 2-6 hours.
[0019] The technical solution for the application of the sodium ion battery hard carbon negative electrode material of the present invention is:
[0020] An application of a sodium ion battery hard carbon negative electrode material, using the sodium ion battery hard carbon negative electrode material to prepare a negative electrode sheet of a sodium ion battery.
[0021] Preferably, the preparation method of the negative electrode plate comprises: adding an organic solvent to the hard carbon negative electrode material, conductive agent and binder in a mass ratio of 90-95:1-5:1-5 to form a slurry with a certain viscosity, setting the coating thickness to 100-200 μm, and forming a negative electrode plate after drying and rolling. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the hard carbon negative electrode material of Example 6 of the present invention;
[0023] Figure 2 This is the XRD diagram of the hard carbon negative electrode material of Example 6 of the present invention;
[0024] Figure 3 This is the first cycle charge and discharge curve of the hard carbon negative electrode material of Example 6 of the present invention. DETAILED DESCRIPTION
[0025] A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: mixing a carbon source precursor and an acid solution to obtain a mixed solution, circulating the mixed solution under the action of a circulating pump, acid washing the carbon source precursor, filtering, washing and drying, and then carbonizing the carbon source precursor under an inert atmosphere.
[0026] In a specific embodiment, the carbon source precursor is coarsely crushed by jaw crusher and roller crusher, and finely crushed by air flow crushing; the carbon source precursor can be first crushed into particles by jaw crusher and roller crusher, and the particle size is less than 2 mm, mixed with an acid solution to complete acid washing, and then crushed to D by air flow crushing. 50 The carbon source precursor can also be directly crushed to D by jaw crusher, roller crusher and air flow crushing. 50 The surface of the nanostructured carbon fiber is 4 to 15 μm, and then mixed with an acid solution to complete pickling, followed by carbonization treatment.
[0027] In a specific embodiment, the airflow pulverization is performed by using an airflow mill.
[0028] In a specific embodiment, the acid solution contains at least hydrochloric acid and hydrofluoric acid. The acid solution can be a mixed acid of hydrochloric acid and hydrofluoric acid, or a mixed acid of hydrochloric acid, hydrofluoric acid and another acid. When the other acid is nitric acid, the acid solution is a mixed acid of hydrochloric acid, hydrofluoric acid and nitric acid. At this time, the mass fraction of hydrochloric acid in the mixed acid is 3-4wt%, the mass fraction of hydrofluoric acid is 0.5-1wt%, and the mass fraction of nitric acid is 0.5-1wt%.
[0029] In a specific embodiment, when the acid solution is hydrochloric acid and hydrofluoric acid, the carbon source precursor can be directly pickled in a mixed acid solution composed of hydrochloric acid and hydrofluoric acid; the carbon source precursor can also be first pickled in one acid solution and then pickled in another acid solution, and the pickling with two acids is completed continuously.
[0030] In a specific implementation, the circulation pump will rub against the material to increase the slurry temperature. After uniform mixing, the temperature is no higher than 90° C., and the pickling temperature is no longer set.
[0031] In a specific embodiment, the heating rate of the carbonization treatment is 0.5°C / min to 10°C / min, and after the carbonization treatment is completed, the furnace is cooled to below 80°C.
[0032] In a specific embodiment, after the carbonization treatment is completed, the hard carbon negative electrode material is sieved, and the sieve mesh number is 350-450 meshes.
[0033] In a specific embodiment, the inert atmosphere is nitrogen, and the oxygen content is less than 50 ppm.
[0034] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.
[0035] 1. Specific embodiments of the method for preparing the hard carbon negative electrode material for sodium ion batteries of the present invention
[0036] Example 1
[0037] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0038] The coconut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to D50 of 8μm and ash value of 3.48%. 60kg of mixed acid of 3wt% dilute hydrochloric acid and 0.5wt% hydrofluoric acid is added to a 200L PP reactor. A shear pump is used for circulating acid washing. 15kg of coconut shell carbonized material is added within 2min. After circulating for 1min, a uniformly dispersed slurry is obtained. The circulation is continued for 15min and then stopped. The acid washing of the carbonized material is completed.
[0039] The above-mentioned coconut shell carbonized material that has completed acid washing is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C, at which time the ash value is 0.22%. It is then carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is <50ppm, and the temperature is increased to 1250°C at a heating rate of 2°C / min, and the carbonization time is 4h. After the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0040] Example 2
[0041] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0042] The coconut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to D50 of 5μm and ash value of 3.48%. 60kg of 3wt% dilute hydrochloric acid is added to a 200L PP reactor, and a shear pump is used for circulating acid washing. 15kg of coconut shell carbonized material is added within 2min, and then circulated for 1min to obtain a uniformly dispersed slurry. The circulation is continued for 15min and then stopped. The filter cake after pressure filtration is placed in a reactor, 50kg of 1% hydrofluoric acid is added, and the shear pump is circulated for 5min to complete the acid washing of the carbonized material.
[0043] The above-mentioned coconut shell carbonized material that has completed acid washing is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C, at which time the ash value is 0.20%, and then carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is <50ppm, and the temperature is increased to 1250°C at a heating rate of 2°C / min, and the carbonization time is 4h. After the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0044] Example 3
[0045] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0046] The semi-coke is crushed by jaw crusher, roller crusher and air flow mill to D50 of 5μm and ash content of 7.89%. 60kg of mixed acid of 4wt% dilute hydrochloric acid, 1wt% hydrofluoric acid and 1wt% nitric acid is added to a 200L PP reactor. A shear pump is used for circulating acid washing. 12kg of semi-coke is added within 2.5min. After circulating for 1min, a uniformly dispersed slurry is obtained. The circulation is continued for 30min and then stopped to complete the acid washing of the semi-coke.
[0047] The above-mentioned blue charcoal that has completed acid washing is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C, at which time the ash value is 0.58%. It is then carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is <50ppm, and the temperature is increased to 1400°C at a heating rate of 2°C / min for 4 hours. After the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0048] Example 4
[0049] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0050] The anthracite is crushed by jaw crusher, roller crusher and air mill to a D50 of 5μm and an ash value of 5.73%. 60kg of a mixed acid of 3wt% dilute hydrochloric acid, 1wt% hydrofluoric acid and 1wt% nitric acid is added to a 200L PP reactor. A shear pump is used for circulating acid washing. 12kg of anthracite is added within 2.5min. After circulating for another 1min, a uniformly dispersed slurry is obtained. The circulation is continued for 30min and then stopped to complete the acid washing of the anthracite.
[0051] The above-mentioned acid-washed anthracite is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C, at which time the ash value is 0.42%. It is then carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is <50ppm, and the temperature is increased to 1200°C at a heating rate of 2°C / min for 4 hours. After the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0052] Example 5
[0053] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0054] The anthracite is crushed by jaw crusher and roller crusher to a particle size of less than 2mm. 60kg of a mixed acid of 3wt% dilute hydrochloric acid, 1wt% hydrofluoric acid and 1wt% nitric acid is added to a 200L PP reactor. A shear pump is used for circulating acid washing. 12kg of anthracite is added within 1min, and the circulation is continued for 30min before stopping. The acid washing of the anthracite is completed.
[0055] The above-mentioned acid-washed anthracite is filtered and washed until the pH of the filtrate is neutral, the filter cake is dried at 120°C, and crushed by air flow mill to D50 of 5μm, at which time the ash value is 0.60%, and then carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is <50ppm, and the temperature is increased to 1200°C at a heating rate of 2°C / min, the carbonization time is 4h, and after the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0056] Example 6
[0057] The method for preparing the hard carbon negative electrode material for a sodium ion battery of this embodiment comprises the following steps:
[0058] The walnut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to D50 of 5μm and ash value of 2.93%. 60kg of mixed acid of 2wt% dilute hydrochloric acid and 0.5wt% hydrofluoric acid is added to a 200L PP reactor, and a shear pump is used for circulating acid washing. 15kg of walnut shell carbonized material is added within 3min, and a uniformly dispersed slurry is obtained by circulating for another 1min. The circulation is continued for 20min and then stopped, and the acid washing of the carbonized material is completed.
[0059] The above-mentioned walnut shell carbonized material that has completed acid washing is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C, at which time the ash value is 0.15%. It is carbonized at high temperature in a nitrogen atmosphere, and the oxygen content is <50ppm. The temperature is raised to 1400°C at a heating rate of 2°C / min, and the carbonization time is 4h. After the carbonization is completed, the temperature is cooled to below 80°C, and the carbonized material is taken out and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0060] The microscopic morphology of the hard carbon negative electrode material obtained in this example is shown in Figure 1 As shown in Figure 2, irregular particle distribution is obtained after air flow milling. Figure 2 As shown, the two peaks at 2θ of 24° and 44° correspond to the diffraction characteristic peaks of the (002) and (100) crystal planes of the carbon material, which are typical amorphous carbon materials.
[0061] 2. Comparison
[0062] Comparative Example 1
[0063] In this comparative example, the carbon source precursor is not acid-washed. The preparation method of the sodium ion battery hard carbon negative electrode material in this comparative example comprises the following steps:
[0064] The coconut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to a D50 of 8 μm and an ash value of 3.48%. It is carbonized at high temperature in a nitrogen atmosphere with an oxygen content of <50 ppm. The temperature is raised to 1250°C at a heating rate of 5°C / min for 4 hours. After the carbonization is completed, the temperature is cooled to below 80°C, the carbonized material is taken out, and passed through a 400-mesh sieve to obtain a hard carbon negative electrode material for a sodium ion battery.
[0065] Comparative Example 2
[0066] The carbon source precursor of this comparative example is pickled under the action of magnetic stirring. The preparation method of the sodium ion battery hard carbon negative electrode material of this comparative example comprises the following steps:
[0067] The coconut shell carbonized material was crushed by jaw crusher, roller crusher and air flow mill to D50 of 8 μm and ash value of 3.48%. 60 mL of mixed acid of 4 wt% dilute hydrochloric acid and 1 wt% hydrofluoric acid was added to a 100 mL beaker, 15 g of coconut shell carbonized material was added by magnetic stirring, and dispersed evenly for 10 min, heated to 80 ° C, kept warm for 1 h and 4 h respectively, filtered and washed until the pH of the filtrate was close to neutral, and the filter cake was dried at 120 ° C. At this time, the corresponding ash values were 0.85% and 0.37%, respectively. It was carbonized at high temperature under nitrogen protection, with an oxygen content of <50 ppm, and heated to 1400 ° C at a rate of 2 ° C / min for 2 h. After carbonization, it was cooled to below 80 ° C, and the carbonized material was taken out and passed through a 400 mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0068] Comparative Example 3
[0069] The carbon source precursor of this comparative example is pickled under ultrasonic action. The preparation method of the sodium ion battery hard carbon negative electrode material of this comparative example comprises the following steps:
[0070] The coconut shell carbonized material was crushed by jaw crusher, roller crusher and air flow mill to D50 of 8 μm and ash value of 3.48%. 60 mL of mixed acid of 4 wt% dilute hydrochloric acid and 1 wt% hydrofluoric acid was added to a 100 mL beaker, 15 g of coconut shell carbonized material was slowly added in batches under ultrasonic vibration, ultrasonic vibration was performed for 1 h and 2 h at room temperature, respectively, filtered and washed until the pH of the filtrate was close to neutral, and the filter cake was dried at 120°C. At this time, the corresponding ash values were 0.76% and 0.35%, respectively. High-temperature carbonization was carried out under nitrogen protection, and the oxygen content was <50 ppm. The temperature was increased to 1400°C at a rate of 2°C / min for 2 h. After carbonization, the temperature was cooled to below 80°C, and the carbonized material was taken out and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0071] Comparative Example 4
[0072] The carbon source precursor of this comparative example is pickled under mechanical stirring. The preparation method of the sodium ion battery hard carbon negative electrode material of this comparative example comprises the following steps:
[0073] The coconut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to D50 of 8μm and ash value of 3.48%. 12kg of mixed acid of 4wt% dilute hydrochloric acid and 1wt% hydrofluoric acid is added to a 25L PP reactor and heated to 80°C. 4kg of coconut shell carbonized material is slowly added in batches under mechanical stirring, and dispersed evenly for 1.5h. The mixture is kept warm and stirred for 4h, filtered and washed until the pH of the filtrate is close to neutral. The filter cake is dried at 120°C, at which time the ash value is 0.32%. It is carbonized at high temperature under nitrogen protection, with an oxygen content of <50ppm. The temperature is increased to 1250°C at a rate of 2°C / min for 4h. After carbonization, the temperature is cooled to below 80°C. The carbonized material is taken out and passed through a 400-mesh sieve to obtain a hard carbon negative electrode material for a sodium ion battery.
[0074] Comparative Example 5
[0075] The carbon source precursor of this comparative example is pickled in only one acid solution. The preparation method of the sodium ion battery hard carbon negative electrode material of this comparative example comprises the following steps:
[0076] The coconut shell carbonized material is crushed by jaw crusher, roller crusher and air flow mill to D50 of 8μm and ash value of 3.48%. 60kg of 3.5wt% dilute hydrochloric acid is added to a 200L PP reactor, and a shear pump is used for circulating acid washing. 15kg of coconut shell carbonized material is added within 2min, and then circulated for 1min to obtain a uniformly dispersed slurry. The circulation is continued for 15min and then stopped, and the acid washing of the carbonized material is completed.
[0077] The above-mentioned coconut shell carbonized material that has been acid-washed is filtered and washed until the pH of the filtrate is neutral, and the filter cake is dried at 120°C. At this time, the ash value is 0.48%, and the removal effect of the impurity silicon element is poor. Then, it is carbonized at high temperature in a nitrogen atmosphere, wherein the oxygen content is less than 50ppm, and the temperature is increased to 1250°C at a heating rate of 2°C / min, and the carbonization time is 4h. After the carbonization is completed, the temperature is cooled to below 80°C, and the carbonized material is taken out and passed through a 400-mesh sieve to obtain a sodium ion battery hard carbon negative electrode material.
[0078] The pickling process parameters of the embodiments and comparative examples are shown in Table 1.
[0079] Table 1 Pickling process parameters of the embodiments and comparative examples
[0080]
[0081]
[0082]
[0083] The pickling time includes the time of adding raw materials, the dispersion time and the continuous pickling time; the pickling efficiency refers to the mass of raw materials pickled per unit time. As can be seen from Table 1, the pickling method in the preparation method provided by the present invention greatly improves the pickling efficiency by 1 to 3 orders of magnitude compared with other pickling methods on the basis of the carbon source precursor reaching a similar ash value.
[0084] The ash value refers to the yield of the residue after the carbon source precursor is completely burned, indicating the content of minerals in the carbon-containing material, and can be used to evaluate the pickling effect. The ash values before and after pickling of the embodiments and comparative examples are shown in Table 2.
[0085] Table 2 Comparison of ash values before and after pickling of the embodiment and the comparative example
[0086] Ash value before pickling (%) Ash value test time (min) Ash value after pickling (%) Example 1 3.48 18 0.22 Example 2 3.48 23 0.20 Example 3 7.89 33.5 0.58 Example 4 5.73 33.5 0.42 Example 5 - 31 0.60 Example 6 2.93 24 0.15 Comparative Example 1 3.48 - - Comparative Example 2 3.48 70 / 250 0.85 / 0.37 Comparative Example 3 3.48 60 / 120 0.76 / 0.35 Comparative Example 4 3.48 330 0.32 Comparative Example 5 3.48 18 0.48
[0087] The ash content test time refers to the ash content value tested at the last few minutes during the pickling process. The ash content value obtained from the test is the ash content value after pickling.
[0088] It can be seen from Table 2 that the pickling method in the preparation method of the present invention can effectively remove impurities in the raw materials and reduce the ash value. Other pickling methods require twice as much time to obtain similar ash values.
[0089] 3. Specific Examples of Application of the Hard Carbon Anode Material for Sodium Ion Batteries of the Present Invention
[0090] Example 7
[0091] In this embodiment, the sodium ion battery hard carbon negative electrode material is used to prepare the negative electrode sheet of the sodium ion battery. The preparation method of the negative electrode sheet is as follows: the hard carbon negative electrode material, the conductive agent SP, and the binder PVDF are added with NMP in a mass ratio of 92:3:5 to form a slurry with a certain viscosity, and the coating thickness is set to 100 μm. After drying and rolling, the negative electrode sheet is formed.
[0092] The preparation method of the sodium ion battery of this embodiment comprises: using the negative electrode sheet prepared above as the negative electrode, using metallic sodium as the counter electrode, using 1 mol / L NaPF6 PC / DEC / EC (1:1:1) solution as the electrolyte, and using a glass fiber filter paper membrane GF / C as the diaphragm to assemble into a 2032 button battery.
[0093] IV. Experimental Examples
[0094] In this experimental example, the sodium storage performance of the button cell prepared in Example 7 was tested, and its charge and discharge performance was tested at a current density of 0.1C and 25mA / g. Figure 3This is the first cycle charge and discharge curve of the hard carbon negative electrode material obtained in Example 6. The first cycle charge and discharge gram-specific capacity and coulombic efficiency of the hard carbon negative electrode material are obtained through the charge and discharge curve. The results are shown in Table 3.
[0095] Table 3 First cycle charge and discharge gram specific capacity and coulombic efficiency of the embodiments and comparative examples
[0096]
[0097] It can be seen from Table 3 that the hard carbon negative electrode after acid washing has a higher first-cycle charge and discharge gram-specific capacity and first-cycle coulombic efficiency, indicating that the acid washing successfully removes metal impurities in the carbon source precursor and avoids the influence of metal impurities on the reversible capacity of the sodium ion battery; compared with Comparative Examples 2-4, Example 1 has a higher first-cycle charge and discharge gram-specific capacity and first-cycle coulombic efficiency, indicating that compared with other acid washing methods, the preparation method provided by the present invention shows a better acid washing effect on the basis of high acid washing efficiency.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: The carbon source precursor and the acid solution are mixed to obtain a mixed solution, and the mixed solution is circulated under the action of a circulating pump until the acid washing of the carbon source precursor is completed. After filtering, washing and drying, the carbon source precursor is carbonized under an inert atmosphere; the circulating pump is selected from a centrifugal pump, a screw pump, a shear pump, a smooth pump, an emulsifying pump, a pneumatic diaphragm pump, and a high viscosity pump; the acid washing time is 10 to 50 minutes.
2. The method for preparing the hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: The acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, acetic acid and citric acid.
3. The method for preparing the hard carbon negative electrode material for sodium ion battery according to claim 2, characterized in that: The mass fraction of the acid solution is 0.5-5wt%.
4. The method for preparing the hard carbon negative electrode material for sodium ion battery according to claim 3, characterized in that: The acid solution contains at least hydrochloric acid and hydrofluoric acid, and the mass fraction ratio of the hydrochloric acid to the hydrofluoric acid is 2-3:0.5-1.
5. The method for preparing the hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: The carbon source precursor is selected from one of coal and carbonized material, the coal is selected from one or more of anthracite, bituminous coal, lignite, and semi-coke, the carbonized material includes one or more of fruit shell carbonized material, charcoal, bamboo charcoal, resin carbonized material, and polymer carbonized material, and the fruit shell in the fruit shell carbonized material is selected from one of coconut shell, walnut shell, peach shell, jujube shell, apricot shell, cherry shell, pistachio shell, and macadamia shell.
6. The method for preparing the hard carbon negative electrode material for sodium ion battery according to claim 1, characterized in that: The particle size of the carbon source precursor is less than 2 mm.
7. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The solid content of the carbon source precursor in the acid solution is 5-30%.
8. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The particle size D of the carbonized carbon source precursor 50 The carbonization treatment temperature is 1000-1600°C, and the treatment time is 1-10h.
9. An application of a hard carbon negative electrode material for a sodium ion battery, characterized in that: The negative electrode sheet of a sodium ion battery is prepared using the sodium ion battery hard carbon negative electrode material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Wild pepper hard carbon sodium / potassium ion negative electrode material as well as preparation method and application thereof
CN108975304A
Hard carbon cathode material and preparation method thereof, and application of hard carbon cathode material
CN110148734A
Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof
CN113381013A